THE INFLUENCE OF WORLD LANGUAGES ON CULTURE - Gaybulloyev , Shakhriyor; Saitov , Sirojiddin (Effective scientific journals, 2026)
Language is not only a tool of communication, it is the heart of culture and the historical memory of a people. Every language embodies the traditions, values, and worldview of its speakers, and through language individuals express not only their thoughts but also their identity and national belonging. This article examines the influence of world languages on culture, highlighting how globally widespread languages such as English, Spanish, Chinese, Arabic, and French have expanded beyond their regions of origin and influence societies through education systems, mass media, literature, trade, and international communication. These languages strengthen interaction among nations and promote knowledge exchange as well as intercultural cooperation. However, linguistic globalization is a complex process because while it creates new opportunities and brings people closer together, it also places smaller and local languages at risk of extinction. The dominance of global languages may gradually lead to the disappearance of certain national languages along with their associated customs, oral traditions, and historical memory, raising concerns about cultural homogenization and its potential consequences.